A comparative study of Mantoux test and BCG test in diagnosis of childhood tuberculosis - Chatterjee, Kripasindhu; Mandal, Pradyut Kr; Rahaman, Sk. Rafikul; Dutta, Amit; Karmakar, Mrinal Kanti; Banoth, Narshima Rao (International Journal of Contemporary Pediatrics, 2018)
Background: India has one of the highest tuberculosis (TB) burdens globally. However, few studies have focused on TB in young children, a vulnerable population, where lack of early diagnosis results in poor outcomes. Methods: The present study was undertaken to assess the sensitivity and specificity of tuberculin test (Mantoux) and BCG test in diagnosis of childhood tuberculosis and to compare above tests as a diagnostic tool and to assess the impact of factors affecting the test. Mantoux test was done with 1 TU contained in 0.1 ml of PPD R23 with tween 80 solution. BCG test was done using a heat stable freeze-dried vaccine, after fresh reconstitution and injected intradermally in left deltoid region with a tuberculin syringe and 27 G hypodermic needle. Results: Tuberculous cases were more common in malnourished subjects more so with severe malnutrition. While maximum positivity 89% was obtained with BCG test, it was only 63% with Mantoux test, done with 5TU of PPD-RT-23. BCG was always positive whenever PPD was positive in any group of children. Sensitivity of Mantoux test was around 63% whereas that of BCG test was 89%. BCG test was more significantly associated with disease than tuberculin test (p <0.001). Conclusions: BCG test is a very sensitive and specific test for diagnosis of childhood tuberculosis. Mantoux test is affected by malnutrition and severity of disease whereas BCG test is affected only minimally. BCG test is more sensitive than Mantoux test (with 5TU PPD RT 23 Tween 80). A BCG induration of ≥10 mm or Mantoux induration ≥15 mm or an accelerated BCG test is indicative of active disease, irrespective of vaccination status of the patient.